Effect of P Application Rate and Rhizobium Inoculation on Nodulation, Growth, and Yield Performance of Chickpea (Cicer arietinum L.) - Mebrahtu Gebremariam; Teklay Tesfay (International Journal of Agronomy)
Chickpea (Cicer arietinum L.) is the world’s third most vital food legume after beans and peas in production level. Yet, its productivity in the last decade has been declined, and it has been contended that the usual native soil rhizobial populations are insufficient/ineffective in N2-fixation. Rhizobium inoculation of the seed may substitute costly N-fertilizers and provide a useful way of achieving sustainable production. Hence, to supply an adequate rhizobial population in the rhizosphere, seed inoculation of chickpea with an effective and importunate rhizobial strain is essential in soils having no/feeble bacterial existence and has revealed optimistic effect on nodule number and mass, growth, yield, and its attributes over uninoculated ones. Its effect has been influenced by N content and P-deficiency of soil, rhizobium strain, variety, T°, pH, salinity, and moisture stress. Phosphorus (P) demand is high in chickpeas, and P deficiency also has a negative effect on chickpea production success. Several research results revealed significant effects of P rate (30–200 kg P2O5 ha−1) on nodule number, mass, and rating plant−1; LAI, RGR, DM, plant height, and branches plant−1; pods and grains plant−1, grain and biomass yields, 100-grain weight, and HI compared to the control. P rates response has been affected by moisture level, pH, available P and N, and variety. Particularly, joint use of P rate and rhizobium inoculation on chickpea has been stated to improve nodulation, growth, and yield and soil fertility. Various studies on the integrated use of P rate and rhizobium inoculation under varying situations showed enhanced nodulation, growth, and yield over the P rate or rhizobium inoculation alone. This might be attributed to adequate P supply and improved utilization with the provision of suitable N2-fixing bacteria for enhanced nodulation and adequate N supply.